The Role of BAZNAS Cirebon City in Promoting the Eco-nomic Independence of Mustahik Through Digital-Based Productive Economic Programs - Selly Silviawati; Triana Apriani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research investigates the strategic role of the National Amil Zakat Agency (BAZNAS) of Cirebon City in fostering economic independence among mustahik (zakat recipients) through productive zakat programs that incorporate digital technology. The focus of this study is to explore how BAZNAS' empowerment initiatives go beyond simply providing capital by integrating structured business mentoring and facilitating digital transformation to stimulate entrepreneurial progress. By employing a qualitative approach with a case study framework, the research examines the real impact of BAZNAS' programs on the livelihoods of mustahik. Data for the study were gathered through semi-structured interviews with 12 mustahik participants, program coordinators from BAZNAS, and local field facilitators. Additionally, observations during entrepreneurship workshops and analysis of official documentation provided supplementary data to strengthen the research findings. The study reveals three key outcomes: increased access to business capital for productive ventures, a growing adoption of digital tools in the operations of micro-enterprises, and enhanced financial independence achieved through business development. The findings show that BAZNAS Cirebon City has effectively contributed to improving mustahik's business management skills, expanding their access to digital markets, and supporting sustainable entrepreneurship. These efforts align with the broader goal of zakat-based empowerment, especially in the context of digitalization. The study emphasizes that the integration of digital tools is vital to empower mustahik and increase their productivity, as it enhances their ability to reach broader markets and manage their businesses more efficiently. Furthermore, the research offers practical recommendations aimed at expanding digital literacy among mustahik, promoting technology-based entrepreneurship, and improving the delivery of digital financial services within zakat distribution programs. These recommendations seek to enhance the overall effectiveness of zakat-based empowerment initiatives in the digital age.